Developmental mechanisms in the prodrome to psychosis. (17th December 2013) - Walker, Elaine F.; Trotman, Hanan D.; Goulding, Sandra M.; Holtzman, Carrie W.; Ryan, Arthur T.; McDonald, Allison; Shapiro, Daniel I.; Brasfield, Joy L.
Abstract: Psychotic disorders continue to be among the most disabling and scientifically challenging of all mental illnesses. Accumulating research findings suggest that the etiologic processes underlying the development of these disorders are more complex than had previously been assumed. At the same time, this complexity has revealed a wider range of potential options for preventive intervention, both psychosocial and biological. In part, these opportunities result from our increased understanding of the dynamic and multifaceted nature of the neurodevelopmental mechanisms involved in the disease process, as well as the evidence that many of these entail processes that are malleable. In this article, we review the burgeoning research literature on the prodrome to psychosis, based on studies of individuals who meet clinical high risk criteria. This literature has examined a range of factors, including cognitive, genetic, psychosocial, and neurobiological. We then turn to a discussion of some contemporary models of the etiology of psychosis that emphasize the prodromal period. These models encompass the origins of vulnerability in fetal development, as well as postnatal stress, the immune response, and neuromaturational processes in adolescent brain development that appear to go awry during the prodrome to psychosis. Then, informed by these neurodevelopmental models of etiology, we turn to the application of new research paradigms that will address critical issues in future investigations. It is expected that these studies will play a major role in setting the stage for clinical trials aimed at preventive intervention.